Hydraulic characteristics of semi- circular sharp crested weirs - Edan I. Ghadban (Tikrit Journal of Engineering Sciences, 2013)
In this research the hydraulic characteristics of sharp crested weirs with semi- circular shape were studied, the study was depended on the dimensional analysis which confirmed by experimental work. The dimensional analysis results demonstrate that the effective parameters on the discharge of flow over this type of weir are the ratio of water height above the weir crest to the radius of this weir (H/R) and the ratio of water height above the weir crest to the height of the crest (H/P). Experimental tests were carried out on (16) models of weirs with Semi-circle shape where the radius of cutting was change four times (R=5, 10, 15, 20 cm) and for any radius the height of the crest was change four times (P= 30, 25, 20, 15 cm). The results show a great influence of the parameter (H/R) on flow parameter (Q2/gH5) while the effect of the parameter (H/P) is limited. Depending on non-dimensional parameters and experimental results, the statistics program (SPSS) were used to create empirical equation for measuring the discharge over the sharp crested weirs with semi-circular shape. The results of the equation show a very good agreement with the experimental result for determine the discharge with knowing the depth of water over the weir (H) , radius of cutting of the weir (R) and height of the crest (P). Also the equation shows a great influence of the radius (R) and limited influence of the height (P) on the discharge over this type of weirs.